Outer nuclear layer relevance in visual function correlated to quantitative enface OCT parameters in Stargardt disease. Issue 6 (November 2021) - Mucciolo, Dario Pasquale; Lippera, Myrta; Giorgio, Dario; Sodi, Andrea; Passerini, Ilaria; Cipollini, Francesca; Virgili, Gianni; Giansanti, Fabrizio; Murro, Vittoria
Purpose: To evaluate the correlation between Best Corrected Visual Acuity (BCVA) and the following parameters in Stargardt Disease (STGD): Central Retinal Thickness (CR-T), Central Outer Nuclear Layer Thickness (C-ONL-T), Areas of macular Photoreceptor loss (PHRa), and Retinal Pigment Epithelium (RPE) loss (RPEa). Methods: A total of 64 eyes of 32 STGD patients were included in the study. All patients received a comprehensive ophthalmological examination, color fundus photographs, fundus auto-fluorescence imaging, and Optical Coherence Tomography (OCT). The CR-T and C-ONL-T were evaluated from standard SD-OCT scans. The PHRa and RPEa were calculated from enface OCT scans (sub RPE slab and photoreceptor slab). The collected OCT parameters were evaluated for possible association with BCVA. Results: The mean macular PHRa and RPEa was 16.16 ± 13.36 and 12.05 ± 12.57 mm 2 respectively. The mean CR-T measured 120.78 ± 41.49 μm while the mean C-ONL-T was assessed at 4.60 ± 13.73 μm. BCVA showed the highest correlation with the C-ONL-T ( r  = −0.72; p  < 0.001) while there was no correlation with the CR-T ( r  = −0.17; p  = 1.00). Conclusions: Enface OCT permits a rapid and precise quantitative evaluation of the macular PHR and RPE atrophy area in STGD. Nonetheless, the OCT parameter that showed the highest correlation with visual acuity in STGD was the ONL thickness.